EPR as an Accelerator for Circular Economy in India’s Plastic Waste Management Industry: A systematic review of literature (Journal of Informatics Education and Research, 2025)
The concept of Extended Producer Responsibility (EPR) has emerged as a transformative policy tool aimed at addressing the environmental impacts of post-consumer waste by transferring the end-of-life responsibility of products to producers. EPR plays a central role in driving sustainable waste management practices, fostering circular economy principles, and reducing the burden on local governments. This study undertakes a Systematic Literature Review (SLR) to trace the evolution of EPR, evaluate its implementation across diverse geographical regions and industrial sectors, and identify the key challenges and opportunities it presents. A total of 63 peer-reviewed academic publications, dissertation thesis and policy documents were examined to build a comprehensive understanding of EPR’s policy mechanisms, institutional arrangements, stakeholder roles, and economic implications. Descriptive trend analysis using Microsoft Excel was applied to categorize the literature by publication year, geographic focus, research methodology, and thematic concentration. The review reveals significant variation in EPR policy effectiveness, influenced by regulatory design, enforcement capacity, producer compliance, and consumer participation. It also underscores a growing research focus on digitalization in EPR processes, traceability mechanisms, and innovations in reverse logistics. Notably, there exists a limited body of research addressing the unique implementation challenges in developing countries, particularly concerning the informal sector, weak enforcement structures, and limited producer awareness. By synthesizing global insights and highlighting existing knowledge gaps, this study contributes to both academic discourse and policy development by offering direction for future research and strategic policymaking aimed at enhancing the efficiency and equity of EPR frameworks.